Social capital, survival strategies, and their potential for post-conflict governance in Liberia - Amos Sawyer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
This paper investigates how people created, adapted and used social capital and conflict resolution during more than a decade of violent conflict in Liberia, and the potential of such capital to contribute to post-conflict peacebuilding and self-governance. – institutions ; conflict ; community ; society ; reconstruction
Keywords: D74; P48; O17; 330